The world turned upside down : America, China, and the struggle for global leadership - Prestowitz, Clyde V., 1941- (New Haven : Yale University Press, 2021)
An authority on Asia and globalization identifies the challenges China's growing power poses and how it must be confronted. When China joined the World Trade Organization in 2001, most experts expected the WTO rules and procedures would liberalize China and make it "a responsible stakeholder in the liberal world order." But the experts made the wrong bet. China today is liberalizing neither economically nor politically but, if anything, becoming more authoritarian and mercantilist. In this book, notably free of partisan posturing and inflammatory rhetoric, renowned globalization and Asia expert Clyde Prestowitz describes the key challenges posed by China and the strategies America and the Free World must adopt to meet them. He argues that these must be more sophisticated and more comprehensive than a narrowly targeted trade war. Rather, he urges strategies that the U.S. and its allies can use unilaterally without contravening international or domestic law.
Includes bibliographical references and index.
Keywords: Globalization -- China -- History -- 21st century; China -- Economic policy -- 2000-; China -- Economic conditions -- 2000-; China -- Politics and government -- 2002-; China -- Foreign economic relations -- United States; United States -- Foreign economic relations -- China; China -- Foreign economic relations